Digital socialism and cyber-communism in the Fourth Industrial Revolution - Gayozzo, Piero (2023)
Socialism is a political ideology that proposes that the State must have control over the means of production to manage a planned economy. The possibility that this thesis can be materialize has been the subject of debate throughout the 20th century. The Fourth Industrial Revolution includes technologies, such as artificial intelligence or Big Data, that could reopen the debate through the formulation of new models of digital planned economies. This qualitative research provides a brief approach to some theoretical models proposed to update socialism in the Fourth Industrial Revolution. Six new forms of digital socialism are described: the Platform Economy, Socialist Feedback Infrastructure, Algorithmic Central Planning, Cyber-communism, Fully Automated Luxury Communism (FALC), and Open-Loop Economic Planning. nature. The need to continue the analysis of these models to enrich the study of political ideologies and the debate about the future of society is concluded.